A cirurgia plástica e reconstrutiva em oncologia. - J M Rego; J Rosa (Acta Médica Portuguesa, 1998)
The authors are members of the surgical staff of a central hospital specialized in the treatment of cancer (Portuguese Institute of Oncology-Francisco Gentil, Lisboa). They present their experience as plastic and reconstructive surgeons, mostly in the use of current reconstructive possibilities, after excision surgery or in a later phase. The aim is to offer the best quality available, which is evaluated by morbidity, mortality and quality of life. Most of the patients are subjected to different series of oncologic therapy, which is submitted to a multidisciplinary decision.